Population Dynamics and Its Implication on Development in Iringa Municipality, Tanzania - Mataro, Zelda M.; Myeya, Helena E.; Kamangu, Abdallah A. (Tanzania Journal for Population studies and Development, 2020)
This study investigates the implications of population dynamics on development in Iringa Municipality Tanzania. A total of 209 respondents were involved in this study. The study used both quantitative and qualitative techniques in collecting and analyzing data where household surveys, in-depth interviews, field observations, Focus Group Discussions and documentary review were used as data gathering techniques. Descriptive statistics and content analysis have been used in analyzing and presenting the collected data. The study findings reveal that Iringa Municipality is experiencing an increase in population as per study time frame (1990 to 2019) has been triggered by inmigration though increased birth rates and reduced mortality rates cannot be neglected. The study further revealed that population growth in the Municipality has positively resulted to increased income levels, market expansion, improvement of social services, increased savings and investments, increased skilled workforce as well as increased urbanization. However, negatively, population growth has triggered high commodity prices, increased rental bills, the spread of diseases, a high number of street children and increase of delinquency behaviours. The study concludes that there is an increase in population associated with in-migration in Iringa Municipality which has brought both positive and negative effects on economic development. It is recommended to use the existing opportunity of population growth for economic development meanwhile, finding out measures which are associated with negative effects of population growth to achieve sustainable development.